Molecular Cloning, Sequence Characterization and Expression Analysis of a CD63 Homologue from the Coleopteran Beetle, Tenebrio molitor - Patnaik, Bharat Bhusan (Molecular Diversity Preservation International (MDPI), 2013)
CD63, a member of the tetraspanin membrane protein family, plays a pivotal role in cell growth, motility, signal transduction, host-pathogen interactions and cancer. In this work, the cDNA encoding CD63 homologue (TmCD63) was cloned from larvae of a coleopteran beetle, Tenebrio molitor. The cDNA is comprised of an open reading frame of 705 bp, encoding putative protein of 235 amino acid residues. In silico analysis shows that the protein has four putative transmembrane domains and one large extracellular loop. The characteristic “Cys-Cys-Gly” motif and “Cys188” residues are highly conserved in the large extracellular loop. Phylogenetic analysis of TmCD63 revealed that they belong to the insect cluster with 50%–56% identity. Analysis of spatial expression patterns demonstrated that TmCD63 mRNA is mainly expressed in gut and Malphigian tubules of larvae and the testis of the adult. Developmental expression patterns of CD63 mRNA showed that TmCD63 transcripts are detected in late larval, pupal and adult stages. Interestingly, TmCD63 transcripts are upregulated to the maximum level of 4.5 fold, in response to DAP-type peptidoglycan during the first 6 h, although other immune elicitors also caused significant increase to the transcript level at later time-points. These results suggest that CD63 might contribute to T. molitor immune response against various microbial pathogens.